Mental health and well-being during COVID-19 lockdown: A survey case report of high-level male and female players of an Italian Serie A football club. (16th November 2021) - Ivarsson, Andreas; McCall, Alan; Mutch, Stephen; Giuliani, Alessia; Bassetto, Rita; Fanchini, Maurizio
ABSTRACT: Objectives: To describe high-level footballers' levels and changes in mental health and well-being throughout a 8-week period of lockdown and restricted training during the COVID-19 pandemic. Method: One-hundred and one players belonging to four teams (women's and men's, first and U19 teams) of the same Italian Serie A club participated in the study. Data were collected through an online questionnaire, and administered at 2, 3, 5, 7 and 9 weeks after the start of the lockdown . Well-being, positive and negative affects measurements were examined. Results: Across the five measures, 36% of players reported clinical levels in depressive symptoms (scores ≤50) on at least one occasion. Thirteen percent of the players reported clinical levels on > 50% of the occasions. There was a decrease in depressive symptoms and negative affects over the period. No change was found in positive affects. Conclusions: High number of players reportedclinical levels of depressive symptoms compared to what was found previously in high-level athletes. The number decrease during the 8-week period. A similar trend was found for negative affects.Despite a higher prevalence in depressive symptoms earlier during lockdown, this improved as players progressed towards fewer restrictions.